2012
DOI: 10.1007/s10856-012-4818-9
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin microparticles aggregates as three-dimensional scaffolding system in cartilage engineering

Abstract: A three-dimensional (3D) scaffolding system for chondrocytes culture has been produced by agglomeration of cells and gelatin microparticles with a mild centrifuging process. The diameter of the microparticles, around 10 μ, was selected to be in the order of magnitude of the chondrocytes. No gel was used to stabilize the construct that maintained consistency just because of cell and extracellular matrix (ECM) adhesion to the substrate. In one series of samples the microparticles were charged with transforming g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 42 publications
(43 reference statements)
1
17
0
Order By: Relevance
“…These results indicated that GEL has accelerated the proliferation and differentiation of MSCs cells. This positive effect of GEL on cell proliferation has been reported in the literature . Another cause might be an RGD sequence of GEL, as a denatured collagen, that improved cell adhesion.…”
Section: Resultssupporting
confidence: 79%
“…These results indicated that GEL has accelerated the proliferation and differentiation of MSCs cells. This positive effect of GEL on cell proliferation has been reported in the literature . Another cause might be an RGD sequence of GEL, as a denatured collagen, that improved cell adhesion.…”
Section: Resultssupporting
confidence: 79%
“…Microsphere (MS)-mediated growth factor delivery has been used for years to mature and differentiate many engineered tissues, including cartilage ( Solorio et al, 2010 ), bone ( Wang et al, 2009 ), and stem cell aggregates ( Carpenedo et al, 2009 ; Solorio et al, 2010 ; Bratt-Leal et al, 2013 ). MS incorporation alone can increase tissue strength ( Solorio et al, 2012b ; Dikina et al, 2015 ), oxygen diffusion ( Hayashi and Tabata, 2011 ; Tajima and Tabata, 2013 ), cell viability ( Garcia Cruz et al, 2013 ; Tajima and Tabata, 2013 ), and uniformity of matrix deposition ( Solorio et al, 2012a ). However, their application in vascular tissue engineering has been limited.…”
Section: Controlled Release From Tissue Engineered Blood Vesselsmentioning
confidence: 99%
“…At this phase, the preparation of any drugs or biological agents is done and later mixed with the gelatin aqueous solution. For protein encapsulation by gelatin, the preheated gelatin solution is cooled down to body temperature to avoid protein denaturation, or by applying the protein solution onto the GM [ 42 , 43 ]. The gelatin solution is mixed with preheated oil and stirred to obtain the water in oil emulsion.…”
Section: History and Characteristics Of Gelatin Microspherementioning
confidence: 99%